La géographie selon LinkedIn. L’exemple de la région SUD. - Aurélia Bernard; Cyrille Genre-Grandpierre (Netcom)
LinkedIn is a professional social network that facilitates information exchanges and networking among its members. Based on the user profiles, the platform's algorithm assigns them to a municipality, a sector, or a region, thus drawing up a spatial polarization. However the logic of the resulting partition of space is difficult to follow: the assignments vary for a given municipality, and the partitions obtained do not correspond to those of traditional geography. As these assignments potentially determine the establishment of contacts between members, they may induce performative effects on the labor market. In this current work, we therefore seek to better describe and understand them. The polarizations of the platform were revealed using a database on LinkedIn members in the SUD region. They were then compared to traditional geography partitions. Finally, we study the differences in LinkedIn polarizations depending on the jobs of the platform's members.